Predicting the effects of demographic factors on email satisfactory communication - Anumudu, Chinedu Eugenia; Yasin, Megat Al Imran; Ahmad Ghazali, Akmar Hayati; AlSagoff, Syed Agil (Universiti Putra Malaysia Press, 2020)
Although empirical studies on information and communication technology have affirmed that Nigerian academic staff used email as the most useful internet product for accomplishing clerical tasks, email related studies so far researched in Nigeria seemed to have focused less on ascertaining if demographic factors could have effects on email satisfactory communication. Therefore, this study examined if demographic factors had effects on email satisfactory communication among South-East Nigerian academic staff. The quantitative research approach was used because the study engaged in descriptive and inferential studies. We found that the respondents' gender affected email satisfactory communication. However, the other four demographic factors that comprised age, job status, educational level, and working experience years did not have significant effects on email satisfactory communication. In terms of management patterns, the study established that more than half of the respondents rarely clean junk emails. Moreover, the findings demonstrated that the majority of them did not set up smart folders for moving joke and advertisement related-emails. Our study further indicated that more than half of the respondents were not strategically managing incoming emails. We, therefore, recommend that South-East Nigerian academic staff should consider regularly cleaning junk emails, setting up folders for moving jokes and advertisements related-emails, and adopting strategies for managing incoming emails if they anticipated achieving more email satisfactory communication. Conclusively, our findings contributed to understanding the effects of demographics factors on email satisfactory communication and other virtual communication technologies in addition to their effective management.